Preparation and Characterization of Lauric–Myristic Acid/Expanded Graphite as Composite Phase Change Energy Storage Material. (17th June 2021) - Zhou, Dongyi; Yuan, Jiawei; Xiao, Xianghua; Liu, Yicai
Abstract : Lauric acid (LA) and myristic acid (MA) were used to prepare a binary eutectic mixture. The expanded graphite (EG) was used as the carrier, and the lauric–myristic acid/expanded graphite (LA–MA/EG) composite phase change material was prepared by physical adsorption method. The microstructure, chemical structure, and thermal properties of LA–MA/EG were characterized by scanning electron microscopy (SEM), differential scanning calorimeter (DSC), Fourier transform infrared spectroscopy (FTIR), and thermal conductivity measurement. The experimental results have shown that the maximum mass ratio of the binary eutectic mixture in the LA–MA/EG composite phase change energy-storing material was 92.2%, and there was physical mixing and has no chemical reaction between LA–MA and EG. The fusion point temperature of LA–MA/EG was 33.4°C, the solidification point temperature was 33.8°C, and the latent heat was 171.1 J/g, which was suitable for building energy storage field. After several thermal cycles, the change of the fusion point and potential heat of the composite phase change materials were very small, and it still has good energy storage performance.